Population abundance of recovering humpback whales Megaptera novaeangliae and other baleen whales in Scotia Arc, South Atlantic - Baines, Mick; Kelly, Natalie; Reichelt, Maren; Lacey, Claire; Pinder, Simon; Fielding, Sophie; Murphy, Eugene; Trathan, Phil; Biuw, Martin; Lindstrøm, Ulf; Krafft, Bjørn A.; Jackson, Jennifer A. (Marine Ecology Progress Series, 2021)
Following the cessation of whaling, South Atlantic populations of humpback Megaptera novaeangliae and some other baleen whale species are recovering, but there has been limited monitoring of their recovery in the Scotia Arc, a former whaling epicentre and a hotspot for Antarctic krill Euphausia superba . To inform the management of krill fisheries, up-to-date assessment of whale biomass and prey consumption is essential. Using a model-based approach, we provide the first estimates of whale abundance and krill consumption for South Georgia and the South Sandwich Islands and total abundance of humpback whales across their southwestern Atlantic feeding grounds, using data collected in 2019. Humpback whale abundance was estimated at 24543 (coefficient of variation, CV = 0.26; 95% CI = 14863-40528), similar to that measured in Brazil on the main wintering ground for this population. The abundance of baleen whales in South Georgia and the South Sandwich Islands, including those not identified to species level, was estimated at 43824 (CV = 0.15, 95% CI = 33509-59077). Based on the proportion of humpback whales identified during the surveys (83%), the majority of these are likely to be humpback whales. Annual krill consumption by baleen whales was estimated to be in the range 4.8 to 7.2 million tons, representing 7 to 10% of the estimated krill biomass in the region. However, there is a need to better understand feeding rates in baleen whales, and further research into this field should be a priority to improve the accuracy and precision of prey consumption rate estimation.